The theses for PhD degree - article Editorial (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Ye.S. Ageyeva – Molecular and cellular bases of Helicobacter pylori-associated disease immunopathogenesis at Khakasia population.Yu.V. Embutnieks – Bone mineral density in patients with digestive diseases.